Introduction [In Water Resources Allocation] - Koundouri, Phoebe; Birol, Ekin (Springer, 2011)
This chapter aims to communicate the two main rasons d'etre of this book, namely: (1) to present and analyze the Cyprus experience in water resources management policies (2) communicate this experience to other countries that can inform, develop and improve their water resources policies by understanding the strong and weak elements of the Cyrus experience. Moreover, the chapter introduces the specific themes and issues that are analyzed in the consecutive chapters of the book.